ANALISIS PENANGANAN KREDIT BERMASALAH BANK CIMB NIAGA UNIT SUBRANTAS PEKANBARU (KASUS PENYALURAN KREDIT MIKRO) - Hot Dame Tamba; Lena Farida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Micro Credit on CIMB Bank Unit Subrantas Pekanbaru is credit which aimed for micro entrepreneurs. The purpose of distribution micro credit is to give help fund for micro entrepreneurs in Pekanbaru for developing their bussiness. Credit distribution is never rid of credit risk, that is Non Performing Loan. Non Performing Loan must be handled as soon as possible in order to not give bank suffer a financial loss because the bank does not receive the distribution fund back. CIMB Niaga Bank Unit Subrantas Pekanbaru as micro credit distributor is never rid of Non Performing Loan, so it is need to be handled well.The purpose of this research is to know and analyze the handling of Non Performing Loan on CIMB Niaga Bank Unit Subrantas Pekanbaru (Distribution Micro Credit Case). The method of this research use primary and secondary data with qualitative method which was arranged descriptively. The used sampling technique was purposive sampling. The informants in this research were The Chief of Micro Credit and employee who took in charge of collecting micro credit on CIMB Niaga Bank Unit Subrantas Pekanbaru. To handle Non Performing Loan, CIMB Niaga Bank Unit Subrantas Pekanbaru is needed to do credit restructuring such as restructuring, taking over, and selling collateral.Keyword: Micro Credit, Non Performing Loan, Handling Non Performing Loan